KARAKTERISTIK BENIH DAN PERKECAMBAHAN PEPAYA (Carica pepaya L.) - Muhammad Husaini Assauwab; Mario Pani (Agros Journal of Agriculture Science, 2023)
Papaya (Carica pepaya) is a crucial tropical plant in Indonesian agriculture. Research conducted at the Seed Technology Laboratory of the Universitas Gunung Leuser Aceh revealed variations in the characteristics of papaya seeds, including the number of seeds that varies based on fruit size and seed arrangement. This study provides in-depth insights into the characteristics of papaya seeds and the influencing factors on germination, aiming to enhance seed quality and the optimal growth of papaya plants. Seed color reflects maturity and physiological status, featuring an elongated and egg-shaped form with flattened cotyledons. The germination process is influenced by environmental factors such as temperature, light, pH, oxygen, and soil moisture, with optimal humidity being a key factor for successful germination. The implications encompass a positive contribution to the development of cultivation techniques and sustainable management of papaya plants. Understanding the characteristics of papaya seeds and germination is expected to facilitate the design of more efficient cultivation practices, positively contributing to the growth and competitiveness of papaya plants. This research serves as a foundation for the development of effective seed technology to achieve sustainable plant growth. Keywords: Development, Papaya, Imbibition, Morphology, Seed INTISARIPepaya (Carica papaya L.) merupakan tanaman tropis yang penting dalam pertanian Indonesia. Penelitian di Laboratorium Teknologi Benih Universitas Gunung Leuser Aceh mengungkapkan variasi karakteristik biji pepaya, termasuk jumlah biji yang bervariasi berdasarkan ukuran buah dan tipe letak biji. Penelitian ini memberikan wawasan mendalam terhadap karakteristik benih pepaya dan faktor-faktor yang memengaruhi perkecambahan, bertujuan meningkatkan kualitas benih dan pertumbuhan tanaman pepaya secara optimal. Warna biji mencerminkan tingkat kematangan dan fisiologis, dengan bentuk memanjang dan bulat telur serta kotiledon pipih. Proses perkecambahan dipengaruhi oleh faktor lingkungan seperti suhu, cahaya, pH, oksigen, dan kelembaban tanah, dengan kelembapan sebagai kunci sukses perkecambahan. Implikasinya mencakup kontribusi positif dalam pengembangan teknik budidaya dan pengelolaan tanaman pepaya secara berkelanjutan. Dengan memahami karakteristik benih dan perkecambahan pepaya, diharapkan dapat merancang praktik budidaya yang lebih efisien dan memberikan kontribusi positif pada pertumbuhan dan daya saing tanaman pepaya. Penelitian ini menjadi landasan bagi pengembangan teknologi benih yang efektif guna mencapai pertumbuhan tanaman yang sukses secara berkelanjutan. Kata Kunci: Perkembangan, Kates, Imbibisi, Morfologi, Biji